The Word Dog in German Proverbs and Expression: Linguaculturology Analysis - Borgin, Senja Fithrani (Future Science)
This study examines the word dog used in proverbs and the German expression of the linguaculture approach. The aim of the discussions is to identify the use of dog in proverbs and German expressions and to explain the meaning they contain. It is also intended to explain the meaning of the proverb and the German expression with the relationship of German society. The data were taken from the dictionary DUDEN Redewendung (2008). Presentation of the result of the data analysis presented using the descriptive method. The word dog in German proverbs and expressions has more negative than positive meanings, which means that German society regards dogs as bad animals. This can be explained by its influence on German culture through the linguistic perspective.